Pension Systems, Demographic Change, and the Stock Market - Hillebrand, Marten (Lecture Notes in Economics and Mathematical Systems, 2008)
Due to the accelerating demographic change of the population the reform of the existing pension systems constitutes one of the greatest political challenges in most European countries. A theoretical discussion of different pension reforms must incorporate not only the demographic aspect but also the role of financial market risk and the impact on production and employment. These notes develop a dynamic macroeconomic model which incorporates these aspects within a flexible theoretical framework. The proposed approach provides a large scale population model and features a sound description of the production side as well as of the financial side of the economy and their interactions with the pension system. Within this framework various adjustment policies of the pension system are studied under different population scenarios. The consequences for the economy and the welfare of consumers are analyzed and compared.